Mandar Language Interference towards the Study of Indonesian Phonology in Communicating Students of SMAN 1 Pamboang in Majene District - Subianto Basri; A. Muh. Ayyub Ht (Universitas Muhammadiyah Enrekang, 2024)
This research is field research which aims to determine the form of phonological interference from Mandar in Indonesian for students at SMAN 1 Pamboang , Majene Regency and to determine the factors that cause interference.The research method used is a qualitative descriptive research method, which provides an overview and explanation (explanation) of the form of phonological interference in the Mandarese language in Indonesian students at SMAN 1 Pamboang and the factors that influence it. Data collection was carried out using listening techniques, note-taking techniques and recording techniques. The results of the research show that the form of phonological interference in the Mandarese language in Indonesian occurs in the form of phonetic and phonemic interference in the form of language sound errors, namely the use of the phoneme /e/ which is symbolized by the unrounded central vowel sound [ә]. Factors that cause interference include; speakers' habit of using the first language (Mandarin) and lack of understanding of the elements of the second language Indonesian (BI), the use of the second language (BI) is still felt foreign by most BM speakers when interacting with speakers who use the same code. BM, thus affecting good and correct BI communication patterns and ultimately giving rise to language errors.